Leadership capacity building for sustainable educational reform in the Turkish Republic of Northern Cyprus - Mertkan, Sefika (2010)
This study examines the recent educational reform initiatives in North Cyprus with particular emphasis on (1) building head teachers' capacity to lead instructional development and organisational improvement, and (2) improving the system capacity to support head teachers in the effective undertaking of their roles. The study frames the current domain of headship in North Cyprus within the external system infrastructure in which head teachers operate, illustrates the national framework for building head teachers' capacity to lead, and looks at how the existing opportunities for leadership capacity building can be enhanced, along with the system infrastructure, to provide a context within which the enhanced capacity can be realised. The study employs a mixed-method design with an inductive drive, where the qualitative paradigm has a dominant and the quantitative has a supplemental status. Surveys, qualitative interviews, and documentary analysis were used to answer the research questions the study explores. Findings clearly show that the case of North Cyprus is an instance of 'vernacular globalisation'. Implemented in a very 'glocal' context in response to very particular problems, the reforms are influenced by local histories and narratives of the nation as much as by such global imperatives as the heightened need for up-skilled citizens. The study reveals that head teachers operate within a highly centralised system, which lacks infrastructure, a strong focus on teaching and learning, and credible monitoring and evaluation systems. It is common for heads to spend a significant amount of time dealing with bureaucratic and operational matters, and questions of instruction and professional development seem to be beyond their remit. This is a condition that needs to change. There are also significant problems with the professional development opportunities for head teachers that must be addressed. Keywords: Educational Reform, Educational Change, Educational Leadership, Capacity-Building, Education Policy